Impact of multiparametric magnetic resonance imaging targeted biopsy on functional outcomes in patients following robot-assisted laparoscopic radical prostatectomy - Conrad Leitsmann; Annemarie Uhlig; Felix Bremmer; Mirjam Naomi Mohr; Lutz Trojan; Marianne Leitsmann; Mathias Reichert (Frontiers in Surgery, 2023)
IntroductionMultiparametric magnetic resonance imaging guided prostate biopsy (mpMRI PBx) leads to a higher rate of successful nerve-sparing in robot-assisted laparoscopic prostatectomy (ns-RALP) for prostate cancer (PCa). This study aimed to evaluate the impact of mpMRI PBx compared to standard ultrasound-guided PBx on functional outcomes focusing on erectile function in patients following ns-RALP.Material and methodsAll RALPs performed between 01/2016 and 06/2021 were retrospectively stratified according to (attempted) ns vs. non ns RALPs and were then categorized based on the PBx technique (mpMRI PBx vs. standard PBx). We compared RALP outcomes such as pathological tumor stage, rates of secondary nerve resection (SNR) and positive surgical margin status (PSM). Furthermore, we explored the association between PBx-technique and patient-reported outcomes assessed 12 months after RALP using the prospectively collected 26-item Expanded Prostate Cancer Index Composite (EPIC-26) questionnaire. Chi-square tests and logistic regression analysis were conducted.ResultsA total of 849 RALPs included 517 (61%) procedures with (attempted) ns. Among these, 37.5% were diagnosed via preoperative mpMRI PBx. Patients with a preoperative standard PBx had a 57% higher association of PSM (p = 0.030) compared to patients with mpMRI PBx and a 24% higher risk of erectile dysfunction (ED) 12 months post RALP (p = 0.025). When ns was attempted, we observed a significantly higher rate of SNR in patients who underwent a standard PBx compared to those who received a mpMRI PBx (50.8% vs. 26.7%, p < 0.001) prior RALP. In comparison, upgrading occurred more often in the standard PBx group (50% vs. 40% mpMRI PBx, p = 0.008).ConclusionThe combination of mpMRI PBx for PCa diagnosis followed by ns-RALP resulted in significantly fewer cases of SNR, better oncological outcomes and reduced incidence of ED 1 year after surgery. This included fewer PSM and a lower rate of postoperative tumor upgrading.